Nanostructured Lipid Carrier-Based Delivery of Pioglitazone for Treatment of Type 2 Diabetes - Ilyas, Umair; Asif, Muhammad; Wang, Minglian; Altaf, Reem; Zafar, Hajra; Faran Ashraf Baig, Mirza Muhammad; Paiva-Santos, Ana Cláudia; Abbas, Muhammad (Frontiers in Pharmacology, 2022)
Pioglitazone (PGZ) is utilized as a therapeutic agent in the management of (type 2) diabetes to control blood glucose levels. The existing research work was intended to make and optimize PGZ containing NLCs (nanostructured lipid carriers). The fabricated nanostructured lipid carrier preparation was optimized by using different concentrations of the surfactants (Tween80, Span 80) while keeping the drug (PGZ), solid lipid (Compritol® 888 ATO), Liquid Lipid (Labrasol®) and co surfactants (Poloxamer 188) concentration same. The optimized NLCs formulation (PGZ-NLCs) was further assessed for physical and chemical characterization, in vitro PGZ release and stability studies. The optimized PGZ-NLCs has shown an average diameter of 150.4nm, EE 92.53%, PDI value 0.076, and zeta-potential -29.1 mV, correspondingly. The DSC thermal analysis and XRD diffractograms had not presented the spectrum of PGZ confirming the comprehensive encapsulation of PGZ in lipid core. PGZ-NLCs showed significant extended release (51% in 24 h) than the unformulated PGZ. Our Study findings confirmed that PGZ-NLCs can be a promising drug delivery system for the treatment of type-2 diabetes.